Basidiomycetes macroscópicos da Estação Científica Ferreira Penna, Pará, Brasil - Melo, Odair de Almeida (Museu Paraense Emílio Goeldi, 2023)
The Ferreira Penna Scientific Station (ECFPn) is located in the Caxiuanã National Forest, a conservation unit in the state of Pará, managed by IBAMA, and is administered by the Museu Paraense Emílio Goeldi, occupying an area of 33,100ha of the Caxiuanã National Forest. The vegetation cover of the area is represented, with a predominance of 80%, by terra firme forest, occurring also floodplain forest, igapó forest and natural fields. The present work is part of the project Fungi of the National Forest of Caxiuanã, and this subproject aims to survey the macroscopic fungi found in the area of the Ferreira Penna Scientific Station, in order to have a greater knowledge of the diversity of species of the Fungi Kingdom existing in the Station. The material studied was collected during five field trips made between April 1995 and February 1997, and studied taxonomically for identification of the specimens, following the usual methods for fungi proposed by Fidalgo & Bononi (1984). The identification was performed with the aid of microscopy, through freehand sections, and mounting of slides in 1% fluocsin solution and/or 4% potassium hydroxide (KOH), and melzer reagent for testing amyloid reactions of spores and other structures. A list of 33 species, distributed in 18 genera and 6 phanu1ias, from the 51 specimens identified is presented. The Polyporaceae family had the highest occurrence of species and specimens studied. All the collected material, 542 specimens of fungi from Myxomycota and Eumycota divisions, were added to the João Murça Pires Herbarium (MG) in the Botany Department of MPEG. This will allow future identification and further studies by specialists of the different groups of fungi collected.